Functioning of dialect lexical elements in the texts of the Ukrainian modern prose (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article describes the peculiarities of dialect lexical elements’ functioning in the texts of the Ukrainian postmodern prose. The author shows the specific of using these units in comparison with other non-literary units.
Keywords: dialect lexical elements; Ukrainian postmodern prose